Subfecundity and associated factors among pregnant mothers receiving antenatal care at public health facilities in Ambo town Oromia region, Ethiopia: a cross-sectional study - Andesha, Elias; Abdissa, Gizachew; Ganfure, Gemechu; Adugna, Melese; Sheleme, Merga; Bedane, Jemal (Frontiers in Global Women's Health, 2025)
BackgroundSubfecundity is defined by a time to pregnancy of more than 12 months with unprotected sexual intercourse. Despite many couples experiencing psychological, social, and economic effects as a consequence of subfecundity, it has been inadequately explored in Ethiopia.ObjectiveSince there is limited information available in Ethiopia on subfecundity and no further studies have been conducted in the study area, this study will serve as input. Therefore, this study aimed to assess the magnitude of subfecundity and associated factors in Ambo town.MethodsA cross-sectional study was employed using systematic sampling to select 368 pregnant mothers. Data were collected through face-to-face interviews using a pre-tested structured questionnaire supplemented with a review of medical records. Bivariate and multivariable logistic regression were performed to identify factors associated with subfecundity. The statistical significance was declared using 95% CI, with a p-value <0.05.ResultA total of 361 mothers (21.3%, 95% CI: 17.20–25.50) were interviewed, resulting in a response rate of 98%. Subfecundity was more likely among mothers aged >35 years (AOR = 3.74, 95% CI: 1.38–10.18), menstrual cycle irregularities (AOR = 3.15, 95% CI: 1.66–5.98), those whose coital frequency was 1 day per week (AOR = 4.77 95% CI: 2.22–10.23), mothers with primigravida (AOR = 2.29, 95% CI: 1.18–4.41), those who used contraceptives (AOR = 1.87, 95% CI: 1.02–3.50), and those who were stressed before conceiving (AOR = 1.95, 95% CI: 1.03–3.70).ConclusionThis study found that the prevalence of subfecundity was 77% (21.3%, 95% CI: 17.2–25.5), which is slightly higher than previous findings in Ethiopia. Subfecundity was more likely among mothers age >35, those with primigravida, mothers who experienced menstruation irregularities, those whose coital frequency was less than twice per week, mothers using an injectable contraceptive method, and those who were stressed before the current pregnancy. Thus, health professionals should provide information for women at preconception care clinics, sexual and reproductive health clinics, and family planning clinics to those who wish to become pregnant before the age of 35 years to increase the frequency of coital practice, decrease stress, and encourage treatment for menstruation irregularities.